The Gender and Motives of the Wisdom Teacher in Proverbs 7 - BELLIS, ALICE OGDEN (Bulletin for biblical research, 1996)
The assumption that objectivity is an illusion is often asserted as if it were objectively true. Nevertheless, it is true that male and female commentators sometimes allow gender based biases to hinder their attempts to understand biblical texts in their original contexts. Both gender based and western culture derived assumptions have adversely colored interpreters' understanding of the gender and motives of the wisdom teacher in Proverbs 7. This paper takes a fresh look at the issues and concludes that the teacher is a F(emale) voice whose strategy of changing men's sexual behavior is consistent with high female self esteem and, if successful, would have strengthened the entire community.